2005
DOI: 10.1099/mic.0.28088-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein O-mannosyltransferase A of Aspergillus awamori is involved in O-mannosylation of glucoamylase I

Abstract: Industrially important extracellular enzymes from filamentous fungi are often O-mannosylated. The structure and function of the pmtA (AapmtA) gene encoding the protein O-D-mannosyltransferase of Aspergillus awamori were characterized. The AapmtA disruptant, designated AaPMTA, was constructed by homologous recombination. The strain AaPMTA exhibited fragile cell morphology with respect to hyphal extension, as well as swollen hyphae formation and conidia formation in potato dextrose medium. Moreover, the AapmtA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 45 publications
3
28
0
1
Order By: Relevance
“…Evidence has shown that the PMT family is crucial for viability, cell wall integrity, and morphogenesis in several fungal species, such as S. cerevisiae, S. pombe, C. albicans, and C. neoformans (11,27,33,42). Recently, pmtA, encoding an O-mannosyltransferase of the PMT2 subfamily, was shown to be required for the formation of a normal cell wall in Aspergillus species (25,26). It is assumed that the PMT family is also crucial for the growth and, therefore, virulence of A. fumigatus, as seen for C. albicans and C. neoformans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that the PMT family is crucial for viability, cell wall integrity, and morphogenesis in several fungal species, such as S. cerevisiae, S. pombe, C. albicans, and C. neoformans (11,27,33,42). Recently, pmtA, encoding an O-mannosyltransferase of the PMT2 subfamily, was shown to be required for the formation of a normal cell wall in Aspergillus species (25,26). It is assumed that the PMT family is also crucial for the growth and, therefore, virulence of A. fumigatus, as seen for C. albicans and C. neoformans.…”
Section: Discussionmentioning
confidence: 99%
“…Although the structure of O-linked oligosaccharides present in the cell wall peptidogalactomannan of A. fumigatus has been characterized (20), little is known about the genes responsible for the initiation of O-mannosylation assembly. As a matter of fact, only the pmtA gene, which encodes a member of the PMT2 subfamily, has been studied so far, in Aspergillus nidulans and Aspergillus awamori (25,26). Here we report the functional analysis of Afpmt1 of A. fumigatus.…”
mentioning
confidence: 99%
“…Accordingly, all three pmt genes of A. nidulans contribute to normal hyphal development and are expressed throughout growth, implying that protein O mannosylation plays important roles for this fungal strain. We previously characterized AnpmtA and AapmtA genes encoding PmtA belonging to the PMT2 subfamily (26,27). Here we characterized two Anpmt genes encoding AnPmtB and AnPmtC belonging to the PMT1 and PMT4 subfamilies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Culture filtrates of the transformants were concentrated by centrifugation through Microcon YM-10 (Millipore) filter units and loaded onto sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Detection of GAI was done by immunoblotting using an anti-GAI-antibody as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…At least 23 target proteins have been described in yeasts (15). Only three Pmt target proteins have been described in filamentous fungi (12,23,37).…”
mentioning
confidence: 99%